The characterization of ternary Zn-Ni-Co alloy coatings electrochemically deposited on steel from sulfate solution - Miroslav B. Jokić; Jelena B. Bajat (Zaštita Materijala)
In this work the electrochemical deposition of ternary Zn-Ni-Co alloy coatings on steel from sulfate, additive-free electrolyte, was investigated. The ratio of metal cations [Co2+]/[Ni2+] in the plating solution was analysed, as well as the influence of deposition current densities on the chemical content and corrosion stability of ternary coatings. Coatings were deposited at 25 °C. On the basis of the results obtained it was shown that the cobalt to nickel ratio is alloy coatings is significantly higher as compared to their ratio in the plating electrolyte, indicating beneficial effect of Ni and Co codeposition. Deposition of Zn-Ni-Co alloy coatings from both plating electrolytes analysed in this work was anomalous. The optimal parameters for electrodeposition of ternary Zn-Ni-Co alloy coatings with increased corrosion stability are metal ion ratio [Co2+]:[Ni2+] = 0,46 in the plating bath and deposition at current densities of 3 i 6 A dm-2.